(untitled) (Medical Forum Monthly, 2023)
Objective: To evaluate the post-operative complications and patients satisfaction after surgical extraction of third molar using two different techniques comma incision and standard Wards incision Study Design: Randomized controlled Trial study Place and Duration of Study: This study was conducted at the Dental OPD of Institute of Dentistry, CMH Lahore Medical College, Lahore, from January 2022 to December 2022. Methods: The study included 96 patients with impacted mandibular 3rd molars. Group A (48 patients) had comma-shaped incision surgery, while Group B (48 patients) had Ward's incision surgery. Patients aged 18–45 were selected, except for trismus, pregnancy, oral submucous fibrosis and limited mouth opening. Chi-square and paired t-tests assessed post-operative complications in these surgeries. Results: In group A mean age was 32.5 ± 5.7 years and in group B mean age was 33.2 ± 3.9 years. In Group A, 62.5% are male and 41.7% are female, while in Group B, 37.5% are male, and 58.3% are female. In this study, Group A experienced higher postoperative pain levels than Group B, notably on the 1st and 3rd post-op days, while Group B exhibited faster pain relief by the 7th day. Mouth opening was initially lower in Group A but equalized by the 7th day, and Group A consistently had more swelling, especially on the 1st and immediately post-op days. Pocket depth was higher in Group A immediately post-op and on subsequent days. Furthermore, wound healing was significantly better in Group B. Patient satisfaction showed no significant difference between the two groups. Conclusion: The study found that the newly developed comma-shaped incision design was superior to the traditional method (Ward's incision) because it resulted in fewer complications after surgery.